As it is in Heaven [videorecording (DVD)] - Pollak, Kay, 1938-; Nyqvist, Michael, 1960-2017; Hallgren, Frida, 1974-; Sjöholm, Helen, 1970-; Jähkel, Lennart, 1956- (Lorber Films, 2009)
Daniel, a successful international conductor, returns to his childhood village in Sweden. Soon thereafter, the local church choir seeks him out to solicit his advice. He can't refuse, and nothing in the village is the same again. As the amateur choir develops and grows, he is drawn to the people of his old hometown, makes friends, and finds love.